Erziehung - Körper - Entkörperung Forschungen zur pädagogischen Theorieentwicklung - Wehren, Sylvia (Historische Bildungsforschung, 2020)
The historical and theoretical relationship between education and the body is the focus of this discourse-analytical study. It is situated at the interface of systematic educational science and historical educational research and looks at both the current debate on educational theory and the pedagogical discussions at the end of the 18th century and the beginning of the 19th century. The starting point of the analyses is a theoretical phenomenon called disembodiment. This term refers to different dynamics that in their totality aim at the discursive exclusion and marginalisation of corporeality in the discourse on education. Three works from different currents of pedagogy are examined more closely for this purpose: Campe's 'Allgemeine Revision des gesammten Schul- und Erziehungswesens' (1785-1792), Niemeyer's 'Grundsätze der Erziehung und des Unterrichts' (1796-1824/5) and two writings by Schwarz, the 'Erziehungslehre' (1802-1813) and the 'Lehrbuch der Erziehung und Unterrichtslehre' (1805-1835). In addition to a presentation of the spectrum of perspectives on physical education, a reconstruction of the historical discourse of so-called physical education and case analyses of the anthropological contexts, the study is able to show that disembodiment tendencies can be traced not only in the current discourse, but already at the turn of the 19th century.